A Siloxene/Ecoflex Nanocomposite‐Based Triboelectric Nanogenerator with Enhanced Charge Retention by MoS2/LIG for Self‐Powered Touchless Sensor Applications. (17th March 2022) - Shrestha, Kumar; Sharma, Sudeep; Pradhan, Gagan Bahadur; Bhatta, Trilochan; Maharjan, Pukar; Rana, SM Sohel; Lee, Sanghyun; Seonu, Sookyeong; Shin, Youngdo; Park, Jae Y.
Abstract: The contactless triboelectric nanogenerator with the capability of touchless interactions has become extremely fascinating for applications in health care, remote security, and augmented reality. Herein, a Siloxene/Ecoflex nanocomposite‐based high‐performance contactless triboelectric nanogenerator (TENG) is newly proposed that induces abundant surface charges owing to the strong electron affinity property of the Siloxene/Ecoflex. Furthermore, charge retention is one of the significant challenges in contactless TENG. For this, molybdenum disulfide (MoS2 ) incorporated laser‐induced graphene (LIG) is introduced as a charge trapping interlayer, which increases the surface potential by four‐fold, enhances the output performance of the TENG, and exhibits excellent charge trapping property which is supported by the surface potential measurements. In addition, the fabricated TENG exhibits excellent humidity sensing characteristics with a sensitivity of 0.45 V/% whereas the wear and tear of the device is prevented owing to the non‐contact mechanism of TENG. Finally, the TENG is demonstrated as a self‐powered sensor for touchless hand sanitizer applications as well as a wireless controller that transmits triggering signals for controlling the movement of the object in a gaming interface. Considering the ongoing coronavirus pandemic, the proposed contactless TENG is highly promising for touchless interactions and for reducing possible contact situations. Abstract : A Siloxene/Ecoflex based contactless triboelectric nanogenerator (TENG) is developed for reducing the possible contact situations and improving the robustness and functionality of TENG. A charge trapping interlayer is utilized to improve the charge retention and output performance of the fabricated TENG. Considering the COVID‐19 pandemic, the device is demonstrated as a self‐powered sensor for a touchless hand sanitizer.